2019
DOI: 10.1111/tbed.13109
|View full text |Cite
|
Sign up to set email alerts
|

Peste des Petits Ruminants ( PPR ) virus serological surveillance in goats in Lao PDR : Issues for disease eradication in a low‐resource disease‐free setting

Abstract: Peste des Petits ruminants (PPR) is an economically important transboundary viral disease of goats. This study aimed to determine a baseline of serological evidence for Peste des petits ruminants virus (PPRV) in Lao goats. A total of 1,072 serum samples were collected by convenience sampling across five provinces in Laos and tested for antibody response to PPRV using a commercially available competitive ELISA. Positive antibody responses were found in 2.2% (95% CI 1.4, 3.2) of the samples. True prevalence calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…On screening of the 776 serum samples, the observed apparent and calculated true seroprevalence was 1.16% and -0.005 %, respectively (Table 1) et al, 2017;Acharya et al, 2018;Dayhum et al, 2018;Burns et al, 2019) including some studies from India with varying levels of seroprevalence (Singh et al, 2004a;Raghavendra et al, 2008;Balamurugan et al, 2014a;2020a;Devi et al, 2016). The present study defines the prevalence of SRMV antibodies in small ruminants in Sikkim and generated evidence of a very low apparent seroprevalence, which might be due to the collected random samples were from apparently healthy animals and not from PPR suspected animals.…”
Section: Resultsmentioning
confidence: 96%
“…On screening of the 776 serum samples, the observed apparent and calculated true seroprevalence was 1.16% and -0.005 %, respectively (Table 1) et al, 2017;Acharya et al, 2018;Dayhum et al, 2018;Burns et al, 2019) including some studies from India with varying levels of seroprevalence (Singh et al, 2004a;Raghavendra et al, 2008;Balamurugan et al, 2014a;2020a;Devi et al, 2016). The present study defines the prevalence of SRMV antibodies in small ruminants in Sikkim and generated evidence of a very low apparent seroprevalence, which might be due to the collected random samples were from apparently healthy animals and not from PPR suspected animals.…”
Section: Resultsmentioning
confidence: 96%
“…PPR is a transboundary emerging disease that spreads across broad geographic areas in Asia, Africa, and the Middle East [10]. PPR has become endemic in Morocco, Tunisia, Algeria, Bangladesh, Tanzania, China, and Laos [10][11][12][13][14][15]. In 2021, the first case of PPR in Southeast Asia was recently reported to the WOAH in Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the global eradication of PPR could return benefits of about $74 billion over 15 years [26]. However, the continuous epidemiological cycles of PPR worldwide [27] constitute a great challenge to eradicating the disease. This calls for a deeper understanding of its temporospatial characteristics.…”
Section: Introductionmentioning
confidence: 99%